Innovación de tres postres aplicando técnicas vanguardistas - López Revelo, Camila Elizabeth (2024)
Contemporary gastronomy faces a critical challenge: the lack of innovation in the preparation of desserts, which limits the ability of gastronomic establishments to stand out in a competitive market. This project focused on revitalizing three traditional Ecuadorian desserts-paila ice cream, pineapple cheese and figs with cheese-through the application of avant-garde techniques such as spherification and gelation. The general objective was to transform these desserts into innovative proposals that fused tradition and modernity, enhancing the culinary experience and strengthening business competitiveness. The specific objectives included bibliographic research on advanced culinary techniques, practical elaboration of the selected desserts and evaluation of their acceptance through tastings. The methodology combined an exploratory, qualitative and experimental approach, evaluating gastronomic trends and applying state-of-the-art techniques in the preparation of the desserts. A sensory analysis was carried out to adjust and perfect the preparations. The results revealed that the incorporation of innovative techniques improved the presentation, flavor and texture of traditional desserts, increasing their acceptance among consumers. In addition, these innovations strengthened the positioning of the establishments in the market, standing out for their differentiated gastronomic offer. As a main conclusion, the application of avant-garde techniques to traditional desserts not only enriches the culinary offer, but also boosts creativity in the kitchen, contributing to the economic and tourism development of the country.